1967
DOI: 10.1099/00221287-48-2-269
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Extracellular Melanoproteins of Venturia inaequalis in Host Susceptibility

Abstract: SUMMARYA series of fungal melanoproteins (mol. wt 10,000-70,000) was isolated from culture filtrates of Venturia inaequalis, and partially characterized by gel filtration and acid hydrolysis. Petiole injection of aqueous solutions of the melanoproteins with non-phytotoxic marker compounds, into apple shoots, produced specific effects on the transport of solutes within the leaves. The effects were not reproduced by substitution of melanoprotein by egg-white lysozyme, rabbit haemoglobin, bovine serum albumen or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0
1

Year Published

1973
1973
2017
2017

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 5 publications
0
15
0
1
Order By: Relevance
“…but not pigment. It is concluded that the secretion of pigment into the culture fluid by the fungus was not a consequence of adverse physical growth conditions and may therefore occur in the host as indicated by earlier work (Hignett & Kirkham, 1967).…”
Section: Results a N D Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…but not pigment. It is concluded that the secretion of pigment into the culture fluid by the fungus was not a consequence of adverse physical growth conditions and may therefore occur in the host as indicated by earlier work (Hignett & Kirkham, 1967).…”
Section: Results a N D Discussionmentioning
confidence: 66%
“…
I N T R O D U C T I O NVenturia inaequalis, the apple scab organism, has previously been shown to produce biologically-active proteinaceous pigmented metabolites in culture (Hignett & Kirkham, 1967;Kirkham & Hignett, 1973;Hignett, 1973). The material stimulated the disease when applied as a spray 2 or 3 days after inoculation of test plants; it also showed affinity for ribosomes in vivo and in vitro.
…”
mentioning
confidence: 99%
“…;upport the view that the parasite elaborates substances which may interfere with the functioning of the host cell wall (and hence with solute transport) and also with host metabolisni at the site of protein synthesis. Previous work with fungal pigment and kinetin has indicated that solute transport and the hormone system of infected plants are closely associated with the scab disease, which is also affected by incident light (Hignett & Kirkham, 1967;Kirkharn & Hignett, 1973). Plant hormones have been involved with the ribosomelpolyribosome system (Evins & Varner, 1972;Trewavas, 1968), with RNA and protein synthesis (Srivastava & Arglebe, 1968;VonAbrams & Pratt, 1968), and with the light incident upon the plants (Back & Richmond, 1969;Jackson & Field, 1972).…”
Section: Discussionmentioning
confidence: 99%
“…Coloured substances made by the plant pathogen Venturia inaequalis have been shown to be closely implicated in the progress of the apple scab disease (Hignett & Kirkham, 1967;Kirkham & Hignett, 1973).…”
Section: Introductionmentioning
confidence: 99%
“…Production of extracellular phenoloxidase by V. inaequalis would tend to enhance this effect, thereby inhibiting its growth. The fungus would also be deprived of phenolic substrates, which would hinder its capacity to synthesize melanoprotein which is active in the apple scab disease (Hignett & Kirkham, 1967 ;Hignett, 1973). In view of the generally observed changes in virulence of isolates of I/.…”
Section: R E S U L T S a N D Discussionmentioning
confidence: 99%